2003
DOI: 10.1590/s1415-43662003000100015
|View full text |Cite
|
Sign up to set email alerts
|

Influência dos elementos meteorológicos na produção de adubos verdes, em diferentes épocas de semeadura

Abstract: Para se estudar a influência do saldo de radiação solar, temperatura do ar, precipitação e fotoperíodo no rendimento em fitomassa e na data de florescimento da Crotalaria juncea e da Mucuna aterrima, foi conduzido um experimento em São Vicente da Serra, MT, na área experimental da Escola Agrotécnica Federal de Cuiabá, em 1999 e 2000. O delineamento experimental usado foi o de blocos ao acaso, com três repetições. A mucuna apresentou maiores rendimentos em fitomassa; a relação ETr/ETp foi a variável que melhor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
4
0
4
Order By: Relevance
“…9;2018 There is a reduction of the vegetative cycle with the reduction of the crop cycle, which causes a smaller plant growth period. Results obtained by Santos and Campelo Júnior (2003) demonstrated reduced fresh and dry matter of sunn hemp in later plantings, as well as in experiments performed by Timossi et al (2014). Both authors attribute these effects to photoperiod reduction in cropping cycles with later sowing.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…9;2018 There is a reduction of the vegetative cycle with the reduction of the crop cycle, which causes a smaller plant growth period. Results obtained by Santos and Campelo Júnior (2003) demonstrated reduced fresh and dry matter of sunn hemp in later plantings, as well as in experiments performed by Timossi et al (2014). Both authors attribute these effects to photoperiod reduction in cropping cycles with later sowing.…”
Section: Resultssupporting
confidence: 74%
“…However, we assumed that the sample sizes for the productive traits of this crop cultivated at different sowing dates in the Brazilian subtropical region, site of this study, are different from those obtained by Teodoro et al (2015) because of the influence of environmental factors and sowing dates on the growth and development of sunn hemp plants (Santos & Campelo Júnior, 2003;Timossi, Teixeira, Cava, Goularte, & Nascimento, 2014). We emphasize that reduced sample size can compromise the reliability of the results of the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the field in Araponga faces West and the plot in Pedra Dourada South, so the daylight duration on the field in Araponga is longer, the soil drier, and the adapted plants tend to develop faster. The differences in nutrient content between locations for the same species can be attributed to the ability of each species to adapt to microclimatic conditions (Santos & Campelo Júnior, 2003).…”
Section: Nutrients In Green Manure Biomassmentioning
confidence: 99%
“…Similar results were reported by Timossi, Teixeira and Cava (2014), who found that late sunn hemp sowing shortened vegetative growth and the time to flowering. Santos and Júnior (2003) noted that late sowing decreased mean plant height. The yield reductions were attributed to the sensitivity of this crop to photoperiod (Alcântara, Furtini Neto, Paula, Mesquita, & Muniz, 2000).…”
Section: Resultsmentioning
confidence: 99%